Guest

If 3sinx + 4cosx = 5, then 4sinx - 3cosx =....??? 0 -5 1/5 5 plz explain me in detail... how to do questions like this...

If 3sinx + 4cosx = 5, then 4sinx - 3cosx =....???



  1. 0

  2. -5

  3. 1/5

  4. 5


plz explain me in detail... how to do questions like this... 

Grade:12

9 Answers

KARAN ACHARYA
52 Points
10 years ago

ANS    3sinx+4cosx=5

     => 3/5 sinx +4/5 cosx = 1

     let cosA=3/5   => sinA=4/5

     =>  cosAsinx + sinAcosx = 1

     =>  sin(x+A) = 1

Now,

       4sinx - 3cosx

  =   5(4/5sinx - 3/5 cosx)     [multipying numerator and denominator by 5]

  =   5(sinAsinx - cosAcosx)

  =   -5{cos(x+A)} = -5[root{1-(sin(x+A)^2)}] = -5 x 0 = 0          Ans 0

 

TRICK: if asinx+bcosx is given then multiply numerator and denominator by root(a^2 +b^2)

            this method is useful  in many questions 

 

 

 PLEASE       APPROVE       MY       ANSWER       IF       YOU       LIKE       IT

 

BARATH P
18 Points
9 years ago

3sinx+4cosx=5

Squaring on both sides.

(3sinx+4cosx) 2 = 25

9sin2x +16 cos2x+24sinxcosx=25

9(1- cos2x)+16(1- sin2x)+ 24sinxcosx=25

9-9 cos2x+16-16 sin2x+24sinxcosx=25

25-9 cos2x-16 sin2x+24sinxcosx=25

9 cos2x+16 sin2x-24sinxcosx=0

(3cosx-4sinx) 2 = 0

4sinx-3cosx=0

 

Chandrabhushan Reddy Chigarapalli
25 Points
6 years ago
3sinx+4cosx=5.
Do sqaring on both sides.
The equation will be as :- 9sin2x+16cos2x+24sinx.cosx=25.
Let the above equation be no.1
Think that the value of 4sinx-3cosx=p.
Do squaring on both sides.
The eqation will be as :- 16sin2x+9cos2x-24sinx.cosx=p2.
Let the above equation be no.2
Add equations no.1 and no.2
You will get as :- 25sin2x+25cos2x=25+p2
25(sin2x+cos2x)=25+p2
25=25+p2                                   (because sin2x+cos2x=1)
p2=0
p=0.
4sinx-3cosx=0.
Therefore answer is 0.
 
 
PLEASE  APPROVE  MY  ANSWER  IF IT IS RIGHT
sumanth
32 Points
6 years ago
 

3sinx+4cosx=5

 

Squaring on both sides.

 

(3sinx+4cosx) 2 = 25

 

9sin2x +16 cos2x+24sinxcosx=25

 

9(1- cos2x)+16(1- sin2x)+ 24sinxcosx=25

 

9-9 cos2x+16-16 sin2x+24sinxcosx=25

 

25-9 cos2x-16 sin2x+24sinxcosx=25

 

9 cos2x+16 sin2x-24sinxcosx=0

 

(3cosx-4sinx) 2 = 0

 

4sinx-3cosx=0

Lab Bhattacharjee
121 Points
6 years ago
HINT:  (3sinx +4cosx)^2+(3cosx-4sinx)^2=(3^2+4^2)(cos^2x+sin^2x)
ritesh
31 Points
6 years ago
easiest method....given 3sinx+4cosx=5..then find 4sinx-3cosx=?
a=3  b=4  c=5...let our ans to be k
a^2+b^2=c^2+k^2
after putting values nd solving we get...k=0...easy method...
 
 
Kushagra Madhukar
askIITians Faculty 629 Points
one year ago
Hello student
This question can be solved using two methods both are quite easy
 
Method-1
Given, 
3sinx + 4cosx = 5
Squaring both sides,
9sin2x + 16cos2x + 24sinxcosx = 25
9sin2x + 16 cos2x + 24sinxcosx = 25(sin2x + cos2x)       [ 25 = 25 x1 = 25 x (sin2x + cos2x)
24sinxcosx = 16sin2x + 9 cos2x
or, (4sinx)2 + (3cosx)2 – 2(4sinx)(3cosx) = 0
or, [4sinx – 3cosx]2 = 0
hence, 4sinx – 3cosx =0
 
Method-2
3sinx + 4cosx = 5
as we can notice- 3, 4, 5 are pythagorean triplet therefore are a part of the same right angled triangle.
Dividing both sides by 5
3/5 sinx + 4/5 cosx = 1
If we take 3/5 = cosA ; then sinA = 4/5
or, sinx cosA + cosx sinA = 1
or, sin(x + A) = 1
 
therefore,
cos(x + A) = [1 – {sin(x + A)}2]1/2  = [ 1 – 1 ]½  = 0
cosx cosA – sinx sinA = 0
or, 3/5 cosx – 4/5 sinx = 0
multiplying both sides by -5, we get,
4sinx – 3cosx = 0
 
You can use either of these methods in questions like this. But the 2nd method might be easier in case of some problems.
Hope it helps.
Regards,
Kushagra
Vikas TU
14149 Points
one year ago
Dear student 
Question is not clear 
Please upload an image.
We will happy to help you.
Good luck 
Cheers 
 
Zaid
13 Points
11 months ago
3sinx + 4cosx = 5
as we can notice- 3, 4, 5 are pythagorean triplet therefore are a part of the same right angled triangle.
Dividing both sides by 5
3/5 sinx + 4/5 cosx = 1
If we take 3/5 = cosA ; then sinA = 4/5
or, sinx cosA + cosx sinA = 1
or, sin(x + A) = 1
 
therefore,
cos(x + A) = [1 – {sin(x + A)}2]1/2  = [ 1 – 1 ]½  = 0
cosx cosA – sinx sinA = 0
or, 3/5 cosx – 4/5 sinx = 0
multiplying both sides by -5, we get,
4sinx – 3cosx = 0

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free